The warm hug book - Coleman, William L. (Minneapolis, Minn. : Bethany House, 1985)
A collection of devotions in verse, with related Bible verses, exploring the importance of happy hugs, welcome-home hugs, father-climbing, and other kinds of healthy physical contact.
Keywords: Children -- Prayers and devotions; Hugging -- Juvenile literature; Prayer books and devotions; Hugging